Auditing - Millichamp, A. H. (London : Continuum, Letts Educational, 1996)
This edition includes relevant statements of auditing standards and practice notes. It can be used on the following courses - ACCA, AAT, BTEC, HNC/D in business, finance, and computer studies, BA in accounting and CIPFA. It features short in-chapter case studies, examination questions both with and without answers and a lecturers' supplement.
Includes index.
oif 11/08/15
Loan
Keywords: Auditing; Management accounting